Fronto-amygdala resting state functional connectivity is associated with anxiety symptoms among adolescent girls more advanced in pubertal maturation - Cecile D. Ladouceur; Teague Henry; Amar Ojha; Elizabeth A. Shirtcliff; Jennifer S. Silk (Developmental Cognitive Neuroscience, 2023)
Early adolescence, with the onset of puberty, is an important period when sex differences in anxiety emerge, with girls reporting significantly higher anxiety symptoms than boys. This study examined the role of puberty on fronto-amygdala functional connectivity and risk of anxiety symptoms in 70 girls (age 11–13) who completed a resting state fMRI scan, self-report measures of anxiety symptoms and pubertal status, and provided basal testosterone levels (64 girls). Resting state fMRI data were preprocessed using fMRIPrep and connectivity indices were extracted from ventromedial prefrontal cortex (vmPFC) and amygdala regions-of-interest. We tested moderated mediation models and hypothesized that vmPFC-amygdala would mediate the relation between three indices of puberty (testosterone and adrenarcheal/gonadarcheal development) and anxiety, with puberty moderating the relation between connectivity and anxiety. Results showed a significant moderation effect of testosterone and adrenarcheal development in the right amygdala and a rostral/dorsal area of the vmPFC and of gonadarcheal development in the left amygdala and a medial area of the vmPFC on anxiety symptoms. Simple slope analyses showed that vmPFC-amygdala connectivity was negatively associated with anxiety only in girls more advanced in puberty suggesting that sensitivity to the effects of puberty on fronto-amygdala function could contribute to risk for anxiety disorders among adolescent girls.